MASKULINISASI LARVA IKAN CUPANG (Betta splendens) MENGGUNAKAN JENIS MADU YANG BERBEDA - Febriany Waisapy; Agustina W Soumokil; Brury M Laimeheriwa (Universitas Mataram, 2021)
Male betta fish are more popular and expensive than female betta fish because they have a more beautiful body shape and color. One effort to increase the male fish population is the masculinization method to reverse the sex of the fish to become male, so that the profit value is higher (Siregar, 2018). Generally, sex reversal uses a steroid hormone: 17?-methyltestosterone (MT) by the method: immersion, injection or oral through feed. However, this MT hormone has side effects that can cause pollution, liver damage in test animals and can cause death (Djihad, 2015 in Nazar, 2017). This study was conducted to determine the survival of the larvae and the increase in the percentage of male betta fish by soaking different types of honey. The method used in this study was a laboratory experiment using 3 treatments, namely A (forest honey), B (cattle honey), C (propolis) and 3 replications. Betta fish larvae as test animals were 7 days old, with honey soaked for 10 hours at a concentration of 5ml/L, then reared for 60 days. The results showed that the survival rate of betta fish larvae after honey soaking treatment (10 hours) averaged 100% and the percentage of betta fish survival during maintenance (60 days) ranged from 23-28% where the highest survival was in forest honey ( 28%). Furthermore, the average sex percentage of male sex larvae in the treatment of forest honey immersion (97%), propolis honey (90%), livestock honey (63%) and control (29%). Thus it can be concluded that forest honey is the right type of honey that plays an important role in the masculinization process of betta fish larvae.